Nutrients and heavy metals accumulation in spike and bulb of tuberose (Polianthes tuberosa) under varied wastewater-groundwater irrigation regimes - D S GURJAR; R KAUR; K P SINGH; R SINGH (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted to assess the nutrients and heavy metals accumulation in spike and bulb of tuberose (Polianthes tuberosa L. cv. Prajwal) under varied wastewater-groundwater irrigations regimes at WTC farm of ICAR-Indian Agricultural Research Institute, New Delhi during three consecutive seasons in the years 2013-16. The treatments comprised wastewater irrigation schedules (0.6, 0.8, 1.0, 1.2 and 1.4 ID: CPE), conjunctive use of groundwater and municipal wastewater (at 1.0 ID: CPE) and only groundwater irrigations (at 1.0 ID: CPE) were laid-out in randomized block design with three replication. Major nutrients (N, P and K), micronutrients (Zn, Mn, Cu, Fe) and toxic heavy metals (Ni, Pb, Cd, Cr) concentration in spike and bulb parts of tuberose were analysed as per standard methods. Results indicated that significantly higher contents of macro nutrients (NPK), micronutrients (Zn, Mn, Cu, Fe) and toxic heavy metals (Ni, Pb, Cd, Cr) in both spike and bulb parts of tuberose were recorded under wastewater irrigations scheduled at 1.4 ID/CPE as compared to groundwater irrigation at 1.0 ID/CPE. Hence, irrigation with wastewater may enhanced uptake of nutrients and toxic heavy metals in tuberose due to their higher concentration in wastewater as compared to groundwater.